A battle lost: re-examining the role of German radio intelligence in the Battle of Gumbinnen*. Issue 3 (16th April 2017) - Smoot, Andrew H.
Abstract: The East Prussian Campaign of August 1914 is famous for the intercept of Russian clear-text radio messages by German radio operators. English language accounts have long credited German radio intelligence with providing the information that brought on the Battle of Gumbinnen. However, German and Russian language documents and accounts tell a different story. This paper argues that radio intelligence did not provide the information that led to the Battle of Gumbinnen. Instead, the origins, conduct and aftermath of the battle resulted from intelligence errors that caused the German command authorities to misunderstand the location, structure and intentions of the opposing Russian forces.